Caracterização sistemática do gênero Moenkhausia Eigenmann, 1903 (Characiformes, Characidae) - Raio, Cibele Bender [UNESP] (2014)
The species currently allocated in Moenkhausia are not a monophyletic group. Current studies try to establish new relationships and adequation these species. However, identifications mistakes are usualy verified. What show wrong relationships. This study gathers the taxonomic knowledge of Moenkhausia, fixe, standardizes and complements species descriptions. Most species were grouped into groups, based on characters from the external morphology and phylogenetic knowledge available to the genre: Moenkhausia oligolepis – reticulate patters, presence of dark colored band on the caudal peduncle; M. lepidura – dark spot restricted to the upper lobe of the caudal fin; M. dichroura - spot in both lobes of caudal fin; M. doceana – one horizontally extended humeral spot or two humeral spot, spot presence in the caudal peduncle or in the middle rays of the caudal fin, six or more series of scales above lateral line; M. xinguensis - deep body at origin of dorsal fin, absent or inconspicuous humeral spot, five series of scales above lateral line; M. eigenmanni - concentration of chromatophores on the scales, especially in the middle part of the flanks, usually long body and characteristically convex pre-dorsal region; M. ceros - low concentration of chromatophores on the scales, small, dark or iridescent line from the middle region of the body to the caudal peduncle or middle rays of the caudal fin. These groupings are not natural and should not be taken as phylogenetic relationships. However, they are effective for species identification and development of future hypotheses of relationships in Moenkhausia